Antiparasitic Effect of Carbonnanotubes on Leishmania donovani in vitro - Zghair , Khawla H.; Saheb, Entsar J.; AL-Qadhi , Ban Noori (Iraqi Journal of Science, 2022)
Although several drugs are used against Leishmania infection but they are associated with several adverse complications. Therefore, a new effective treatment needed to be found. In this study, the effect of carbonnanotubes nanoparticles (CNTs NPs) on Leishmania donovani promastigotes was assessed. Viability of promastigotes after adding different concentrations of carbonnanotubes (CNTs) nanoparticles (0.05, 0.1, 5, 10, 20, 40, 60 and 80 μg/ml) to the parasite culture was evaluated by growth rate, viability rate assay and morphological changes. The results indicated that the effect of CNTs NPs on growth rate of promastigotes form. After exposed to 80 μg/ml of CNTs, the growth rate of promastigotes clearly decreased compared with promastigotes treated with the same concentrations of pentostam drug (the standard antileishmanial drug) and the control group. The inhibitory concentration (IC50) of CNTs NPs on promastigotes growth rate was 59.30μg/mL after 72 hours. In addition, CNTs NPs exert cytotoxic effects on L. donovani promastigotes through the induction of their death when exposed to 80μg/ml of CNTs NPs and pentostam. The inhibitory concentration (IC50) of CNTs NPs on L. donovani promastigotes was 53.79μg/mL after 72 hours. The antiparasitic effect increased with the increasing of the CNTs NPs concentration, while the viability curve of the parasite dropped. In addition, a visual inspection by light microscopy has shown that CNTs induces morphological changes in L. donovani promastigotes in comparison to the morphology of the untreated promastigotes. Our data determine the superiority of CNTs as a novel leishmanicidal effect against L. donovani infection over pentostam in vitro.